2020
DOI: 10.1371/journal.pone.0237420
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Wuhan lockdown on the indications of cesarean delivery and newborn weights during the epidemic period of COVID-19

Abstract: Objective To prevent the rapid spread of COVID-19, the Chinese government implemented a strict lockdown in Wuhan starting on 23 January, 2020, which inevitably led to the changes in indications for the mode of delivery. In this retrospective study, we present the changes in the indications for cesarean delivery (CD) and the birth weights of newborns after the lockdown in Wuhan. Methods A total of 3,432 pregnant women in the third trimester of their pregnancies who gave birth in our hospital from 23 January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
94
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 14 publications
6
94
1
Order By: Relevance
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 3592 abstracts screened, 192 were relevant for full-text review and 40 met the inclusion criteria for systematic review ( figure 1 ). 4 , 5 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 A list of excluded studies with reasons for exclusion is provided in the appendix (p 6) . Reporting on resource use or service reconfiguration outcomes is summarised in the appendix (p 27) .…”
Section: Resultsmentioning
confidence: 99%
“…Of the 40 included studies, 31 for which comparable outcomes were also reported in at least one other study were included in the meta-analysis. 4 , 12 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 24 , 25 , 26 , 27 , 28 , 30 , 31 , 32 , 33 , 34 , 37 , 38 , 40 , 42 , 45 , 46 , 47 , 48 , 49 Table 1 shows the characteristics of the 40 included studies, all of which used a historical cohort design. 17 countries were represented, with substantial variation in pandemic mitigation measures among countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations